2021
DOI: 10.3389/fendo.2020.621888
|View full text |Cite
|
Sign up to set email alerts
|

Centrosomes: Til O-GlcNAc Do Us Apart

Abstract: The centrosome apparatus is vital for spindle assembly and chromosome segregation during mitotic divisions. Its replication, disjunction and separation have to be fine-tuned in space and time. A multitude of post-translational modifications (PTMs) have been implicated in centrosome modulation, including phosphorylation, ubiquitination and acetylation. Among them is the emerging O-linked N-acetylglucosamine (O-GlcNAc) modification. This quintessential PTM has a sole writer, O-GlcNAc transferase (OGT), and the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Cytoplasmic O-GlcNAcylated proteins are vital in cell homeostasis partly by modulating the functions of the mitochondrion ( Zhao et al, 2016 ) and centrosome ( Yuan et al, 2021 ). It was found that O-GlcNAcylation extensively stabilized proteins in these two organelles ( Figure 6E ).…”
Section: Resultsmentioning
confidence: 99%
“…Cytoplasmic O-GlcNAcylated proteins are vital in cell homeostasis partly by modulating the functions of the mitochondrion ( Zhao et al, 2016 ) and centrosome ( Yuan et al, 2021 ). It was found that O-GlcNAcylation extensively stabilized proteins in these two organelles ( Figure 6E ).…”
Section: Resultsmentioning
confidence: 99%
“…Some mitochondrial proteins were reported to be O- GlcNAcylated, , and O- GlcNAcylated proteins in the mitochondrion had bidirectional changes in diabetes . Recently, it was found that O- GlcNAcylation modified proteins in the centrosome, the lysosome, and on the cell surface can regulate cell cycle, cancer progression, and cell–matrix interactions. It is of great interest to use glycoproteomic strategies to systematically identify and quantify protein O- GlcNAcylation in these cellular compartments. Despite the technical difficulties to isolate these organelles, the proximity labeling methods, such as APEX, TurboID, and BioID, could accelerate the investigation of compartment-specific O- GlcNAcylation. …”
Section: Quantitative Glycoproteomics For Studying the Properties And...mentioning
confidence: 99%
“…Multi-omics approaches, including lipidomics and glycomics, can also be used to identify novel components involved in the formation of primary cilia and lipid raft-mediated signalling. For example, O-linked β-N-acetylglycosaminylation (O-GlcNAcylation) is related to lipid raft-mediated Akt signalling [120,121] and ciliogenesis [122,123], and is associated with obesity, diabetes and cancer [124][125][126]. Modulation of O-GlcNAcylation may be a novel therapeutic approach to regulate lipid raft dynamics and primary cilia.…”
Section: Therapeutic Approaches Targeting Lipid Raft Dynamics Through Primary Ciliamentioning
confidence: 99%